Strength in women - Guerrini, G (Training sprint canoeing. Progress in improving the physical, technical, tactical, psychological and nutritional preparation, 2015)
Nowadays, the importance of strength development in women is essential to ensure that athletes perform at their maximum potential in each discipline. However, it is necessary to understand such statement through some key factors that, if perceived in the most positive and qualitative manner, will allow the athlete to face sport at her top level. These are the different factors: 1. Cultural - linked to the perception women have of themselves and of the physical changes that come with a sport of great strength impact. It is the concept families and society generally have, including clubs and academies, of a girl who practices a sport often seen as masculine. 2. That related to those real values strength training produces to show the highest level of performance, especially in our sport. From the point of view of the physical condition improvement, strength training is divided in several areas: first, performance, second, that related to prevention linked to performance and to the sports longevity, and third, that related to health during and after their careers as athletes. 3. Performance variation throughout the menstrual cycle. 4. Some of the most common problems in women are known as the Triad. These include: eating disorders, menstruation absence (amenorrhea) and consequently, osteoporosis. 5. Pregnancy and sport.